Building Excellence in Engineering Education in India - DR. NISHA (The journal of contemporary issues in business and government, 2021)
The nation is a member of the Washington Treaty in 2014 and TIER-I institutions have been compulsory to search for accreditation of programmes, promoting universal accreditation recognition of qualifications and make connections of technology institutes all over the world. To put it another way, technology organizations must aim for continued growth enhancement of different machine sub-components that is, input, physical resources, information, person, capital, curricula, teaching processes, production, performance, working-world contact and mechanism for Feedback. India provides the third-largest network tuition, but also faces issues surrounding connectivity, equity and decent pricing. The key problems facing a country include: translating demographic changes into population dividends, growing the Brutch Inscription Ratio (GER) into higher vocational education, ensuring equal access to technical training in various states and classes, including skilled human capital creation, rural development and infrastructure growth. Such organizations have met with extreme scrutiny because of price declines. India’s Government has taken a range of steps in this respect steering. Which include, for example, the State accreditation commission from the AICTE regulatory agency, the introduction of project teachers and training, the proposal on polytechnics under concerted capacity building activity, the drive of ICT, etc. to promote the highest level of technological and economic growth in the country. Adoption at an Institute level must be addressed to improve the quality and develop consistency such as learning and teaching systems, ties with the workforce, full use of resources, the testing environment, personnel preparation in the educational agencies network, and development policy etc. The paper attempts to explain approaches to improve performance and quality in organizations.